Pelatihan Penggunaan Mendeley Reference Dalam Penulisan Karya Ilmiah - Fajrianti, Fajrianti; Kaif, Sitti Hermayanti (Universitas Negeri Gorontalo, 2023)
Writing scientific papers is an essential foundation in the academic sphere, requiring researchers, students, and academics to manage, refer to, and cite various sources that support their arguments and findings. Emerging as a solution to this challenge, Mendeley Reference has the potential to change the way writers manage references in the context of higher education. This Community Service Activity (PKM) aims to provide a more comprehensive understanding to students, especially those in the 7th semester of the PGSD major at the Teaching and Education Faculty of Buton Muslim University, regarding the benefits of using the Mendeley application in writing scientific assignments. This PKM is carried out through three stages: preparation, implementation, and evaluation. The evaluation results showed that most participants had a good understanding, but some required further training. The positive impact of the training can be seen in the academic and professional development of the participants. Therefore, as a follow-up, practical exercises will be intensified, increased structured discussions between participants and presenters, and gathering input from participants for future improvements. Overall, this training significantly contributes to providing students with essential skills in scientific writing and better preparation for future academic and professional challenges.